Cyber security policy in Indonesian shipping safety - Rizki Desiana; Sri Cempaka Prima (Diponegoro University, 2022)
Technological sophistication does not escape cyber threats. The higher the complexity of technology, the more vulnerability to cyber attacks continues to increase. In Indonesia, there are only a few Maritime Cyber Security policies and social security socialisation within government institutions. It needs to become a priority for the government, given the increasing sophistication of technology every year and the growing vulnerability of cyber threats. This study used a qualitative method with a Grounded Theory design, and data collection techniques were literature study and interviews. Cyber regulations in Indonesia are still regulated in the Information Technology and Electronic Law (abbreviated as the ITE Law) or Law number 11 of 2008 and handled by the National Cyber and Crypto Agency. Meanwhile, the regulations related to Maritime Cyber have not given special rules in Indonesia. Several international countries implemented these government policies because they believe in the importance of maritime security. Several international countries have implemented these policies because they believe in the importance of maritime security in cyberspace. This is due to increasingly sophisticated technological developments and the changing times that are increasingly digitising. The Indonesian government must immediately prioritise maritime security issues related to cyber threats in the Indonesian shipping area and establish an institution responsible for cyber problems in Indonesia's maritime space. The existence of rules or policies related to cyber security in the marine space will improve shipping safety and security in Indonesia. In this paper, the author formulates the research problem of how the Indonesian government's policy deals with the threat of Maritime Cyber in the shipping sector in Indonesia.